ORGANIZING INDEPENDENT RESEARCH ACTIVITIES IN CHEMISTRY OUTSIDE THE LESSON - Kosnazarov, Salamat Tanirbergenovich (SCIENCE and SOCIETY, 2026)
This article analyzes various forms of extracurricular activities, including chemistry clubs, project assignments, scientific competitions, and virtual laboratories, and reveals their role in developing experimental skills, critical thinking, and problem-solving skills. The importance of digital technologies and innovative pedagogical methods in creating a flexible and personalized educational environment is considered separately. The obtained results indicate that the systematic organization of independent research activities significantly enhances students' learning motivation, academic performance, and readiness for scientific research.
Keywords: independent research activity; extracurricular learning in chemistry; out-of-class scientific inquiry; student-centered learning; self-directed learning; inquiry-based learning research-oriented education